Effective methods to use audio visual aids for vocabulary learning in first grade students “Salomón Ibarra” elementary school during the first semester of 2019 - Cruz Ráudez, Amy Del Rosario | Jirón, Jacqueling del Carmen | Lagos López, Melida Alicia | Espinoza Barahona, Jeydels Alexander Espinoza Barahona Jeydels Alexander (UNAN-Managua, FAREM-Estelí, Nicaragua, 2019)
The objective of this study is to investigate Effective methods to use audio visual aids for vocabulary learning in first grade students “Salomon Ibarra Mayorga” Elementary school during the first semester of 2019. A qualitative design was selected for this research and two methods of data collection were used: among them is the development of a class using some of the audio visual aids that were found in our research. Class observation and also applied different class plans for evaluation and data collection very useful to complete this study. Among the main points of this investigation are the visual means that facilitate the learning of grammar, particularly flashcard, a type of source that teachers commonly use. In addition, it is important that teachers use different visual aids during the class and keep the student`s attention.